Study the Influence of Solar Activity on the Ionospheric Electron, Ion and Neutral Particle Temperatures over Iraqi Region Using Ionospheric Models - Mardan, Mahmood K.; Hadi, Khalid A. (Iraqi Journal of Science, 2018)
The influence of solar activity on the predicted ionospheric temperature parameters (electron Te, Ion Ti and neutral particle Tn) have been investigated over ionospheric Iraqi region by data generated using International Reference Ionosphere (IRI) and Madrigal models, the models result have been compared during the minimum and the maximum of solar cycle 24 for the years 2009 and 2016 respectively and for an altitudes ranged from 200-1000 km. The region under consideration spans over (latitude 29.1-37.2oN; longitude 38.9-47.7oE) within Iraq territory, the purpose of this paper is to determine the affection of the solar activity represented by the (sunspot number and solar flux) on the annual behaviors of the ionospheric temperature parameters (Te, Ti and Tn).The results of the conducted study showed that the solar activity of the adopted years exhibited a weak affection on the ionospheric temperature parameters, where (Tn) was the highly affected parameter and (Te) was the poorly affected one. Also, the ionospheric temperature parameters were increased with altitudes increment except for (Tn) which was increased with altitudes till 400 km, than it reaches its maximum value and keep constant.